The Influence of Project Managers’ Hard and Soft Competencies on the Success of Fiber Optic Projects in Indonesia with Moderation of Project Managers’ Work Experience - Nurfauziah, Aulia Afifah Ulfah; Rarasati, Ayomi Dita (Borong Newinera Publisher, 2026)
Fiber optic network development is a strategic priority for expanding equitable internet access and supporting socio economic growth. Despite its importance, fiber optic projects often face implementation challenges that create stakeholder conflicts and expose projects to risks that may hinder success. Because fiber optic communication systems are widely used from local to international levels, their implementation demands not only technological readiness but also capable human resources. In this context, project managers are central to project outcomes, and selecting the right manager becomes essential, although the competencies required may differ across organizations and projects. Based on the literature, project managers’ hard competencies, soft competencies, and work experience are considered important factors related to project success. Work experience is also often viewed as a factor that can strengthen employee competencies. Accordingly, this study examines the effects of project managers’ hard and soft competencies on the success of fiber optic projects in Indonesia and tests whether work experience moderates these relationships.This study uses a quantitative survey approach and analyzes the data with Partial Least Squares. The findings show that work experience does not significantly affect the success of fiber optic projects in Indonesia and does not moderate the influence of either hard or soft competencies on project success. In contrast, hard competencies have a positive and significant effect on project success, while soft competencies show a positive but not significant effect. These results indicate that technical competence remains the most decisive factor in the success of fiber optic projects.